2022
DOI: 10.1111/jgh.15994
|View full text |Cite
|
Sign up to set email alerts
|

METTL3 contributes to slow transit constipation by regulating miR‐30b‐5p/PIK3R2/Akt/mTOR signaling cascade through DGCR8

Abstract: Background N6‐methyladenosine (m6A) is the most prevalent methylation modification of eukaryotic RNA, and methyltransferase‐like 3 (METTL3) plays a vital role in multiple cell functions. This study aimed to investigate the role of m6A methylase METTL3 in slow transit constipation (STC). Material and Method The expression of METTL3 and DGCR8 was measured in STC tissues and glutamic acid‐induced interstitial cells of Cajal (ICCs). The effects of METTL3, miR‐30b‐5p, and DGCR8 on the biological characteristics of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Previous studies have shown that METTL3 regulates pyroptosis by regulating autophagy. [21] Whether METTL3 regulates the pyroptosis of BEAS-2B cells by inhibiting autophagy. In vivo assays showed that hyperoxia decreased the protein expression of ATG8 and LC3II/I but increased p62, which was abrogated by METTL3 deficiency ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that METTL3 regulates pyroptosis by regulating autophagy. [21] Whether METTL3 regulates the pyroptosis of BEAS-2B cells by inhibiting autophagy. In vivo assays showed that hyperoxia decreased the protein expression of ATG8 and LC3II/I but increased p62, which was abrogated by METTL3 deficiency ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In PAAD, miR-30b-5p promotes angiogenesis by downregulating GJA1 expression [ 49 ]. In addition, miR-30b-5p promotes cell pyroptosis via the PIK3R2/Akt/mTOR pathway in glutamic acid-induced interstitial cells [ 50 ]. However, little is known about the role of miR-30b-5p in PAAD cells.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Wen-Jing Gong et al. have demonstrated that METTL3 promoted apoptosis, autophagy, and pyroptosis of glutamic acid-induced intrahepatic cholangiocarcinoma (ICC) by interacting with DGCR8 and modulating the miR-30b-5p/PIK3R2 axis in an m6A-dependent manner ( 30 ). METTL3 down-regulation attenuates fusarium-reduced corneal inflammation via PI3K/AKT signaling in mice ( 31 ).…”
Section: Discussionmentioning
confidence: 99%